Biomechanical determinants of rheumatoid arthritis severity and excess cardiovascular disease: common origins of two complex diseases - Stephen Philip Oakley; Samantha Stott; Kerri Gill; Lyanne Weston (RMD Open)
Objectives The determinants of rheumatoid arthritis (RA) severity and excess cardiovascular disease (CVD) are incompletely understood. Biomechanical factors are known to influence RA severity. Articular stiffness correlates with arterial and skin stiffness. This study explored the hypothesis that constitutional stiffness is a common determinant of RA severity and excess CVD.Methods Fifty-eight patients with anti-CCP antibody (ACPA) positive RA and 57 controls were enrolled noting age, sex, body mass index, alcohol and tobacco exposure, Shared Epitope status and in RA disease duration, disease activity, ACPA titre and radiographic damage. Severe RA was defined as radiographic progression >1.3 mSharp points/year or requiring biological disease-modifying antirheumatic drugs (bDMARDs). Articular stiffness (Beighton Score and right 5th metacarpophalangeal (MCP) joint stress–strain responses), carotid-femoral pulse wave velocity and skin extensibility (percent increase distance two dots with manual traction dorsum right hand) were assessed.Results Right 5th MCP stiffness correlated with Beighton Score and with arterial and skin stiffness. High radiographic rate was associated with greater MCP articular (t test p 0.014), arterial (p 0.044) and, in RA <5 years duration, greater skin stiffness (p 0.002) with similar trends in subjects requiring bDMARDs. In RA, arterial stiffness correlated with age (ß p<0.005), articular (ß p<0.001) and skin stiffness (ß p 0.037) and inversely with alcohol consumption (p 0.035).Conclusions Articular, arterial and skin stiffness correlated with each other and with RA severity. As skin is not affected by RA, this association suggests that constitutional stiffness might be a common determinant of RA and CVD. Prospective studies of at-risk preclinical and early RA are required to determine if this relationship is causal.Trials registration number ACTRN12617000170325.